Post-graduation in medicine and allied health sciences in Nepal - Dixit, Sanjaya Mani; Ranjit, Eurek; Dixit, Hemang (Journal of Kathmandu Medical College, 2018)
The history of education in modern medicine in Nepal is not very long. The article tracks development right from the inception of education in modern medicine to various advanced degrees offered in medicine and allied health sciences in Nepal. With the establishment of different provinces and the setting-up of various hospitals and teaching institutions within the country, one can be certain that the objective of training Nepali citizens within the country and providing healthcare to people within Nepal will soon be a reality. An attempt has been made to sum up what already exists in the present scenario within the country so that appropriate action can be taken in the coming years to ensure sufficient human resources for health will be available to meet the World Health Organization’s 2018 slogan of Universal Health Coverage in near future. It also tries to highlight the much needed issue of integrating the professionals from allied health sciences into the existing healthcare system for its further development. There are specialists from different allied professions in the country; their expertise should expand out of academic sector to other sectors as well. The lack of integration of such expertise in patient care seems to be hindering the new developments in the field of healthcare.